Efficiency of the Lung Flute for sputum induction in patients with presumed pulmonary tuberculosis. (13th September 2017) - Sakashita, Kentaro; Fujita, Akira; Takamori, Mikio; Nagai, Takayuki; Matsumoto, Tomoshige; Saito, Takefumi; Nakagawa, Taku; Ogawa, Kenji; Shigeto, Eriko; Nakatsumi, Yasuto; Goto, Hajime; Mitarai, Satoshi
Abstract: Introduction: High quality sputum helps increase the sensitivity of the diagnosis of pulmonary tuberculosis. Objectives: To evaluate the efficiency of the acoustic device (Lung Flute; LF) in sputum induction compared with the conventional method, hypertonic saline inhalation (HSI). Methods: In this crossover study, patients with presumed pulmonary tuberculosis submitted 3 consecutive sputa: the first sputum without induction and the second and third ones using LF and HSI. We compared the efficiency of the 2 induction methods. Results: Sixty‐four participants were eligible. Thirty‐five (54.6%) patients had negative smears on the first sputum without induction. Among those patients, 25.7% and 22.9% patients were smear‐positive after using LF and HSI, respectively ( P  = .001). The positive conversion rate was not significantly different between the methods. The first samples without induction yielded 65.7% positive cultures, whereas 71.4% and 77.1% of the samples from LF and HSI were positive, respectively ( P  = .284). Similar results were observed in the nucleic acid amplification test [no induction (60.0%), LF (72.0%) and HSI (60.0%); P  = .341]. In 29 smear‐positive patients on the first sputum without induction, we observed no significant increase in smear grade, culture yield and nucleic acid amplification test positivity with either method. LF tended to induce fewer adverse events; desaturation (3.1% vs 11.1%; P  = .082) and throat pain (1.5% vs 9.5%; P  = .057). LF showed significantly fewer total adverse events (15.8% vs 34.9%; P  = .023). Conclusions: Our study showed LF had similar sputum induction efficiency to HSI with relatively fewer complications.